A Consensus Routing Algorithm for Mobile Distributed Systems. (18th October 2015) - Arellano-Vázquez, Magali; Benítez-Pérez, Héctor; Ortega-Arjona, J.
This paper introduces a consensus routing algorithm based on an availability function. Such a function obtains a consensus among a group of nodes by evaluating the idle time in the scheduler of each node, along with the general conditions of the network and determining the next step of the route. In this regard, the algorithm proposed here makes it possible to avoid flooding while reducing bandwidth use and keeping changes of the network only at a local scale.